Mechanisms of Cognitive Decline due to White Matter Lesions in Cognitively Intact Older Adults. (20th December 2022) - Taghvaei, Mohammad; Cook, Philip; Khandelwal, Pulkit; Shakibajahromi, Banafsheh; Sadaghiani, Shokufeh; Das, Sandhitsu R.; Brown, Christopher; Tackett, William; Dolui, Sudipto; Shinohara, Russell T.; Wolk, David A.; Detre, John A.
Abstract: Background: White matter hyperintensities (WMH) on FLAIR MRI are highly prevalent in older adults and are linked to cognitive deficits as well as dementia. Likely mechanisms underlying associations between WMH and cognitive deficits include widespread partial disconnection due to the diffuse nature of progressive WMH and/or tract‐specific disconnection syndromes. We used a virtual lesion approach to evaluate cognitive deficits in domains associated with three tracts: left arcuate fasciculus (LAF; verbal working memory), inferior longitudinal fasciculus (ILF; visual processing), and fornix (memory). Method: WMH were semi‐automatically segmented from FLAIR MRI data in 481 ADNI controls and applied as regions of avoidance for probabilistic fiber tracking on DTI data in 46 healthy older subjects from the Human Connectome Lifespan database. Correlations between overall WMH burden or individual tract disruption and global or tract‐domain‐specific cognitive tests were assessed. Tract disconnection was also compared in subgroups with enriched disruption of specific tracts with respect to global WMH burden, Amyloid beta deposition status, and best (>Mean+1SD) versus worst (<Mean‐1SD) test performance. Result: All three tracts showed disconnections due to WMH and the mean tract disconnection increased significantly with overall WMH burden (ILF; p<0.001, LAF: p<0.001, Fornix; p=0.025) (Figure 1A). Also, both overall WMH burden and percent disconnection in ILF were associated with prolonged Trail A and Trail B times after correction for age and education (Table 1). In subgroup analyses, Amyloid beta positive status significantly moderated correlation of Trail B times with overall WMH burden (p=0.007) and ILF disconnection (p=0.020) (Figure 2). Subjects with enriched ILF disconnection (Figure 1B) also had prolonged Trail A times than the average group (34.3 vs 30.2, p=0.003). Based on cognitive tests performance, subjects with better scores on verbal category fluency or verbal logical memory tests had lower LAF (p=0.035) and fornix (Test I; p=0.003, Test II; 0.025) disconnection. Conclusion: While overall WMH burden correlates with cognitive deficits in ADNI controls, significant correlations between specific tract disconnection and tract‐domain‐specific cognitive tests are also observed. Both mechanisms likely contribute to age‐associated cognitive decline. Furthermore, amyloid beta accumulation strengthens these relationships.